„Kto chce roztrzaskać wolność, ten musi tworzyć niewolę”. Polscy socjaliści wobec projektu konstytucji BBWR z lutego 1929 r. (płaszczyzny krytyki i strategie argumentacji) - Piskała, Kamil (Acta Universitatis Lodziensis. Folia Historica, 2015)
The following article analyzes participation of the Polish Socialists in the constitutional debate conducted in the parliament between 1928 and 1930. In the first section, the political context of the debate and main constitutional demands of the Nonpartisan Bloc for Cooperation with the Government are presented. Further, the article discusses role of the constitutional debate in the Polish Socialist Party’s (PPS) political strategy of that time. Leaders of the PPS were arguing that the Nonpartisan Bloc’s constitutional draft was synonymous with the institutionalization of the dictatorial rule in Poland. Socialists criticism of the draft is reconstructed in details in the next few paragraphs. Special attention is given to the discussion about constitutional role of the president and the parliament as well as the connections between class conflicts and political system – main themes in the socialist’s analyzes, presented in the press, mass meetings as well as during parliamentary sessions. In the last part of the article the strategies of argumentation (especially main strategy – discourse polarization) used by socialists leaders, commentators and party’s propagandists are presented and elaborated.